Genetic Diversity of Common Bean (Phaseolus vulgaris L.) Germplasm Resources in Chongqing, Evidenced by Morphological Characterization - Long, Juechen; Zhang, Jijun; Zhang, Xiaochun; Wu, Jing; Chen, Hong; Wang, Ping; Wang, Qiang; Du, Chengzhang (Frontiers in Genetics, 2020)
In this study, 115 common bean germplasm resources were collected from 27 countiesin Chongqing over three years (2015–2017). The results showed that the genetic diversity of the common bean germplasm resources was high, with an average diversity index of 1.447. The diversity of the qualitative traits of each organ was ranked as seed (H’=1.40) > pod (H’=1.062) > plant (H’=0.64) > leaf (H’=0.565), while the diversity of the quantitative traits of each organ was ranked as seed (H’=2.021) > pod (H’=1.989) > phenology (H’=1.941) > plant (H’=1.646). In the cluster analysis, 115 accessions were clustered into four groups. The accessions in the first and fourth group were characteristic of the Andean gene pool, while the accessions in the second group were characteristic of the Mesoamerican gene pool. However, the accessions of the third group possessed the combined characteristics of both gene pools and were thus classified as introgressed type. Four principal components represented 40.30% of the morphological diversity, with the first principal component representing the traits associated with plant growth; the second principal component representing flower characteristics; the third principal component being composed of seed characters; and the fourth principal component representing pod characteristics. The common bean germplasm resources are widely distributed in Chongqing, and the introgressed types are more prevalent in this region than elsewhere, with a rich genetic diversity and high utilization value in genetic breeding.